Postoperative outcomes in vedolizumab‐treated Crohn's disease patients undergoing major abdominal operations. Issue 5 (18th December 2017) - Lightner, A. L.; McKenna, N. P.; Tse, C. S.; Raffals, L. E.; Loftus, E. V.; Mathis, K. L.
Summary: Background: Up to 80% of patients with Crohn's disease require an abdominal operation in their lifetime. As the use of vedolizumab is increasing for the treatment of Crohn's disease, it is important to understand its potential association with post‐operative complications. Aim: We sought to compare 30‐day postoperative infectious complication rate among vedolizumab‐treated Crohn's disease patients vs those who had received TNFα inhibitors or no biologic therapy. Methods: A retrospective review of all Crohn's disease patients who received vedolizumab within 12 weeks of a major abdominal or pelvic operation was performed. Two control cohorts consisted of Crohn's disease patients treated with TNFα inhibitors or no biologic therapy. Results: One hundred Crohn's disease patients received vedolizumab within 12 weeks of an abdominal operation. Vedolizumab‐treated patients underwent an equivalent rate of laparoscopic surgery ( P = .25), had fewer anastomoses performed ( P = .0002), and had equally frequent diversion in the setting of anastomoses ( P = .47). Thirty‐two vedolizumab‐treated patients experienced postoperative infectious complications (32%), 26 of which were surgical site infections (26%). The vedolizumab‐treated group experienced no difference in nonsurgical site infections (6% vs 5% anti‐TNFα and 2% nonbiologic; P = .34), but significantly higher rates of surgical site infections (26% vs 8% and 11%; P < .001). On univariate and multivariate analysis, exposure to vedolizumab remained a significant predictor of postoperative surgical site infection ( P < .001 and P = .002). Conclusions: Twenty‐six per cent of Crohn's disease patients who received vedolizumab within 12 weeks prior to a major abdominal operation experienced a 30‐day postoperative surgical site infection, significantly higher than that of patients receiving TNFα inhibitors or no biologic therapy. Vedolizumab within 12 weeks of surgery remained a predictor of 30‐day postoperative surgical site infection on multivariable analysis. While vedolizumab‐treated Crohn's disease patients may be a sicker cohort of patients, it is important to consider these findings with regard to preoperative counselling, operative timing and primary closure of wounds.